Confocal Raman microscopy and fluorescent in situ hybridization – A complementary approach for biofilm analysis. (October 2016) - Kniggendorf, Ann-Kathrin; Nogueira, Regina; Kelb, Christian; Schadzek, Patrik; Meinhardt-Wollweber, Merve; Ngezahayo, Anaclet; Roth, Bernhard
Abstract: We combine confocal Raman microscopy (CRM) of wet samples with subsequent Fluorescent in situ hybridization (FISH) without significant limitations to either technique for analyzing the same sample of a microbial community on a cell-to-cell basis. This combination of techniques allows a much deeper, more complete understanding of complex environmental samples than provided by either technique alone. The minimalistic approach is based on laboratory glassware with micro-engravings for reproducible localization of the sample at cell scale combined with a fixation and de- and rehydration protocol for the respective techniques. As proof of concept, we analyzed a floc of nitrifying activated sludge, demonstrating that the sample can be tracked with cell-scale precision over different measurements and instruments. The collected information includes the microbial content, spatial shape, variant chemical compositions of the floc matrix and the mineral microparticles embedded within. In addition, the direct comparison of CRM and FISH revealed a difference in reported cell size due to the different cell components targeted by the respective technique. To the best of our knowledge, this is the first report of a direct cell-to-cell comparison of confocal Raman microscopy and Fluorescent in situ hybridization analysis performed on the same sample. An adaptation of the method to include native samples as a starting point is planned for the near future. The micro-engraving approach itself also opens up the possibility of combining other, functionally incompatible techniques as required for further in-depth investigations of low-volume samples. Graphical abstract: Highlights: Raman microscopy provides a priori knowledge for fluorescent in situ hybridization. FISH identification and in vivo compatible Raman spectrum of each microbial cell. Mapping of microbes, chemical composition, biological and non-biological components. Cells appear larger in Raman than in FISH images due to respective signal origin. Technically easy, straight-forward mechanical approach based on micro-engravings.